'Cashew Apple' Juice Blend with Mango, Pineapple and Sapota for Improving Quality of RTS Beverages and Economic Feasibility Thereof - Anindita Roy (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
The present study on value-addition in cashew apple (Anacardium occidentale L.) juice by blending it with mango, pineapple and sapota juices for preparation of RTS beverage was conducted during the year 2012-2013 at Horticultural College and Research Institute, Dr. YSR Horticultural University, Andhra Pradesh, in Completely Randomized Design (CRD) with 3 replications and 10 treatments. In the present investigation, 'cashew apple' juice extracted from the fruit was blended with fruit juices of mango, pineapple and sapota in various proportions. RTS beverages prepared from different blends of cashew apple juice were evaluated for physico-chemical and organoleptic properties at 0, 30 and 60 days of storage, and significant differences were observed. RTS beverage prepared from a blend of 25% cashew apple juice + 75% mango juice (T3) recorded a gradual decrease in pH, titrable acidity and ascorbic acid content from 0 to 60 days after storage, whereas, density of the blended juice increased gradually at 0 to 30 days of storage; thereafter it decreased. Total soluble solids, reducing sugars and TSS/Acid ratio gradually increased from 0 to 60 days of storage, followed by 25% cashew apple juice + 75% pineapple juice (T6). Organoleptic score for RTS prepared from 25% cashew apple juice + 75% mango juice blend (T3), followed by 50% cashew apple juice + 50% mango juice blend (T2), 25% cashew apple juice + 75% pineapple juice blend (T6) and 50% cashew apple juice + 50% pineapple juice blend (T5), were found to be high on quality, viz., colour, taste and overall acceptability, up to 60 days of storage, and were economical for RTS preparation.